De Platão à Kepler: um recorte sobre o movimento dos planetas no sistema solar - Santos, Maria Amanda Guimarães (2023)
The continuous observation of nature makes it possible to build assumptions based on what the senses tell us. Thus, for an observer located anywhere on Earth, the perception that the sky is rotating is quite natural. There is no immediate reason to assume that the Earth is moving. For ancient astronomers, the Earth was huge, stable, immobile and occupied the center of the majestic Universe. In the fourth century BC, the fertile thought of Greek philosophers began to foster a new perception of this Universe. Plato (c. 427-347 BC), considered one of the greatest thinkers of the time, sought an explanation for the cyclical variations observed in the sky, in such a way that he formulated the following problem to his disciples: the stars, eternal, divine and immutable stars , describe perfect, circular trajectories, with uniform speeds around the Earth. However, other celestial bodies, such as the Sun, the Moon and the planets, present complicated trajectories, even, in the case of the planets, describing retrograde movements. So how do you explain these peculiar movements in the sky? In the History of Astronomy, we can assure you that the problem presented by Plato was the starting point that triggered the search for understanding the Universe known until then, sowing theoretical models that were confronted with observational records subject to various errors, carried out until then without the aid of luxury of an optical instrument. What importance did the theories then developed, Geocentric and Heliocentric, have for the History of Science? How are these subjects dealt with in textbooks in the light of the Common National Curriculum Base? From the realization that there is still a great lack of information about ‘Plato’s Problem’ and the associated scientific developments, we propose the construction of the following Educational Technical Products (PTE): (1) Pedagogical Workshop, (2) Scientific Article and (3) Hands-on activity based on the application “Planetary Orbits Simulator from NAAP Labs”.